The effect of palm tocotrienol on surface osteoblast and osteoclast in excess glucocorticoid osteoporotic rat model - Mohamad Fairuz Yahaya; Azizi Zainodin; Reinukaa Pupathy; Ong, Edwin Hock Min; Nurul Husna Abu Bakar; Nor Azimah Zamri; Halim Ismail; Elvy Suhana Mohd Ramli (Penerbit Universiti Kebangsaan Malaysia, 2018)
A balanced interaction between osteoblast and osteoclast plays a major role in maintaining bone strength and structural integrity. Tocotrienol, a palm derivative with potent antioxidant properties showed an anti-osteoporotic effect but little is known about its mechanism of action. Hence, this research was conducted to determine the effects of palm tocotrienol on the surface osteoblast and osteoclast of the the glucocorticoid-induced osteoporotic bones. The study involved 40 male Sprague-Dawley rats weighing 250-300 g which were randomly divided into an equal number of Baseline, Sham, Adrx+Dexa (adrenalectomized with dexamethasone), Adrx+Dexa+ATF (adrenalectomized with dexamethasone supplemented with α-tocopherol) and Adrx+Dexa+PTT (adrenalectomized with dexamethasone supplemented with palm tocotrienol). Bloods were taken prior to sacrifice for serum biomarkers and either tibia or femur was harvested for bone biomarkers, gene expressions analysis and histological studies. A double-blinded experiment was performed to calculate the number of total cells (osteoblasts and osteoclast) with intact nuclei within five fields of view. While serum osteocalcin and gene expression did not show any changes, CTX level was increased in the Adrx+Dexa group but reduced after the supplementation of palm tocotrienol. Supplementation of palm tocotrienol also significantly decrease the osteoclast population (p<0.05) compared to Adrx+Dexa group. In contrast, osteoblast population showed no significant difference across the groups. The result showed that palm tocotrienol acts by modulating the osteoclasts but not osteoblast, which revert the dynamics of bone cells population in the osteoporotic bone to its pre-osteoporotic levels. Supplements of tocotrienol in daily diet may be beneficial in preventing osteoporosis.